2020
DOI: 10.24021/raac.v17i1.5336
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Effect to Glyphosate Based Herbicide - Roundup Original ® - And Nutritional Therapy With Folic Acid and Selenium on Bullfrog (Lithobates Catesbeianus, Shaw - 1802) Cardiac Hytogenesis

Abstract: Os anfíbios são suscetíveis à toxicidade, devido à absorção cutânea dos produtos químicos presentes no ambiente. O uso de herbicidas à base de glifosato é comum e pode ser transportado pelas águas superficiais para os locais de reprodução. O glifosato possui propriedades oxidantes e inibe a ação de enzimas-chave na regulação do ciclo celular. O ácido fólico e o selênio possuem propriedades antioxidantes, que podem reduzir o estresse oxidativo gerado por pesticidas. Ovos de rã-touro (n = 47) foram mantidos em a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, the acute toxicity of glyphosate-based pesticides, as Atanor®, Credit®, Glifloglex®, and Roundup Ultra Max®, was informed in the range of 19.4 mg/L and 78.18 mg/L (Brodeur et al 2014;Soloneski et al 2016). It has been previously demonstrated that glyphosate causes oxidative stress, inhibits the action of key enzymes for regulation of cell cycle, and produces genotoxic damage on amphibian larvae (Carvalho et al 2020;Lima et al 2020). Toxicity studies of 2,4-D on amphibians have shown that the herbicide inhibits oocyte maturation (LaChapelle et al 2007;Stebbins-Boaz et al 2004) and has teratogenic effects on Xenopus laevis (Morgan et al 1996) and Rhinella arenarum, one of the most susceptible amphibian species during the embryo-larval period (Aronzon et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the acute toxicity of glyphosate-based pesticides, as Atanor®, Credit®, Glifloglex®, and Roundup Ultra Max®, was informed in the range of 19.4 mg/L and 78.18 mg/L (Brodeur et al 2014;Soloneski et al 2016). It has been previously demonstrated that glyphosate causes oxidative stress, inhibits the action of key enzymes for regulation of cell cycle, and produces genotoxic damage on amphibian larvae (Carvalho et al 2020;Lima et al 2020). Toxicity studies of 2,4-D on amphibians have shown that the herbicide inhibits oocyte maturation (LaChapelle et al 2007;Stebbins-Boaz et al 2004) and has teratogenic effects on Xenopus laevis (Morgan et al 1996) and Rhinella arenarum, one of the most susceptible amphibian species during the embryo-larval period (Aronzon et al 2011).…”
Section: Introductionmentioning
confidence: 99%